Pathological manifestations in reinforced concrete marquees in some buildings in the city of Garanhuns-PE (Research, Society and Development, 2022)
The modernization of construction techniques accelerated the process of verticalization of constructions in Brazil. With this, he woke up to the need for the construction of marquises on the facades, for the protection and shelter of passers-by. This structure is characterized by presenting little linkage, being of the plate type on the crimped balance, as well as being a structural element that requires special attention due to its configuration and the possibility of sudden rupture. Many are the pathological manifestations located in reinforced concrete marquises, caused by failures in the design, execution and use phases. These pathologies cause wear on the structure, which can lead to collapse. Based on this, this research has as its general objective to carry out an analysis of the pathological manifestations present in reinforced concrete marquises of some buildings located in the city of Garanhuns-PE. The development of the work used an exploratory approach, with bibliographical research, together with a case study. The study was carried out in six marquises, in buildings located in the center of the city. The results obtained show that the inspected marquises presented, in all cases, pathological manifestations originating from the lack of preventive maintenance, where they were compromised to the structural safety and the useful life of the system. This research had as general objective to carry out an analysis of pathological manifestations present in reinforced concrete marquises of some buildings located in the city of Garanhuns-PE, focusing on the characterization of its useful life. The development of the work used an exploratory approach, with bibliographic research together with a case study. In order to obtain the results, an inspection was carried out with the application of a checklist, in eight marquees located in the center of the city. The results achieved with the research show that the inspected marquees present, in most cases, pathological manifestations caused by the lack of preventive maintenance, which compromises the structural configuration and the useful life of part.